Pengaruh Substitusi Tepung Pisang pada Pembuatan Brownies terhadap Sifat Kimia dan Penerimaan Organoleptik - Sifia Silfia (Institution for Industrial Research and Standardization of Industry - Padang, 2012)
Kepok banana (Musa paradisiaca L) is a banana which is usually consumed after being processed first. The banana flesh has a high solid content so that it is very suitable to be made banana flour. Banana flour is obtained from banana fruit flesh through a process of drying and milling. The benefits of banana flours will make it more durable, easier in packing and transportation, more practical for diversifying processed products, to provide added value of banana, and to create business opportunities for the rural agroindustry development. Thus the study was conducted to compare the banana flour with wheat flour. The concentration of banana flour used were 100%, 75%, 50%, 25%, and 0% (control). Products were then analyzed for the crude fiber content, water content, protein, and organoleptic tests were done for taste, aroma, and texture. The results showed that the banana browniez provide the optimum result in treatment when 75% of banana flour was used resulting crude fiber content 1.88%, water content 38.01%, protein content 12.9%, texture, taste and aroma were preferred by the panelists.ABSTRAKPisang kepok (Musa paradisiacal L) merupakan pisang yang biasanya dikonsumsi setelah diolah terlebih dahulu. Daging buahnya memiliki kandungan padatan yang cukup tinggi sehingga sangat cocok untuk dijadikan tepung pisang. Tepung pisang diperoleh dari dagingbuah pisang melalui proses pengeringan dan penggilingan. Manfaat diolah menjadi tepung pisang adalah agar lebih tahan lama, lebih mudah dalam pengemasan dan pengangkutan, lebih praktis untuk diversifikasi produk olahan, memberikan nilai tambah buah pisang, dan menciptakan peluang usaha pengembangan agroindustri pedesaan dan mengurangipenggunaan pemakaian terigu. Penelitian pembuatan brownies pisang dilakukan dengan perlakuan perbandingan tepung pisang dengan tepung terigu. Persentasi tepung pisang yang digunakan adalah 100%, 75%, 50%, 25%, dan kontrol. Produk kemudian dianalisis kadar serat kasar, air, protein, dan uji organoleptik terhadap rasa, aroma, dan tekstur. Hasil penelitian menunjukkan bahwa pembuatan brownies pisang memberikan hasil yang optimal pada perlakuan penggunaan tepung pisang 75% dengan kadar serat kasar 1.88%, kadar air 38.01%, protein 12.09%, tekstur, rasa, dan aroma disukai panelis.